Commitment of Consumers of Certain Psycho-Types of Personality to Various Genres of Video Game Market Products - Nikolay N. MOLCHANOV; Kirill A. YUMASHEV (Communications of International Proceedings, 2023)
The article presents the results of a study the commitment of consumers of certain psychotypes of personality to various genres of video game market products. When developing a marketing campaign, companies need to thoroughly understand their target audience in order to minimize production and marketing risks. Each genre of video games has a number of its own unique features that attract, or, conversely, repel the target consumer. A proposition was put forward about the connection between the psychotype of the consumer and genre preferences. Thus, knowing the psychotype of their target audience, firms can develop a new product for it (or adjust the current one), and vice versa. Having a finished product in their hands, companies can implement it for a specific target audience knowing its psychotype. The video game market has been analyzed; its main target audience has been identified.
Keywords: Marketing research; video game market; digital technologies; digital marketing; personality psychotypes.